2009
DOI: 10.1007/s10997-009-9089-6
|View full text |Cite
|
Sign up to set email alerts
|

Board structures and the establishment of a risk management committee by Malaysian listed firms

Abstract: Corporate governance, Malaysian companies, Risk management, Boards of directors, Internal control,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
74
1
4

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(89 citation statements)
references
References 42 publications
4
74
1
4
Order By: Relevance
“…Therefore, more frequent BOC meetings will increase information and knowledge about the condition of the company, especially the company's risk monitoring and risk management that will affect the implementation of the supervisory function that supports the establishment of the RMC. Yatim (2010) found that the frequency of board meetings had a positive effect with the presence of a RMC. Higher frequency of meetings is associated with a decreased incidence of financial reporting issues and improved quality of external audits.…”
Section: Frequency Of Board Meetings Rmc and Firm Performancementioning
confidence: 97%
“…Therefore, more frequent BOC meetings will increase information and knowledge about the condition of the company, especially the company's risk monitoring and risk management that will affect the implementation of the supervisory function that supports the establishment of the RMC. Yatim (2010) found that the frequency of board meetings had a positive effect with the presence of a RMC. Higher frequency of meetings is associated with a decreased incidence of financial reporting issues and improved quality of external audits.…”
Section: Frequency Of Board Meetings Rmc and Firm Performancementioning
confidence: 97%
“…In line with this, independent members of corporate boards will support the creation of board subcommittees, as such committees may reduce information asymmetries between directors and shareholders and enhance shareholder confidence in firms. Past research reports that independent directors on boards increase the voluntary creation of audit committees (Pucheta‐Martinez & De Fuentes‐Barbera, ), risk management committees (Yatim, ), oversight committees (Cotter & Silvester, ), and board subcommittees (Huang, Lobo, & Zhou, ), among others.…”
Section: Literature Review and Hypothesesmentioning
confidence: 99%
“…Board expertise is imperative in ensuring that the oversight function of the board is successfully carried out (Yatim, 2010). Nadarajan et al (2015) argued that directors that sit on the board of more than one company will acquire more skill, knowledge, and become more expertise in carrying out their oversight functions on managers' activities.…”
Section: Board Expertise and Firm Performancementioning
confidence: 99%
“…Likewise, Yatim (2010) contends that board expertise is imperative in ensuring that the oversight function of the board is successfully carried out. By using a sample of 33 maritime firms quoted in the US for 12-years period (1999)(2000)(2001)(2002)(2003)(2004)(2005)(2006)(2007)(2008)(2009)(2010), Andreou et al (2014) established that the proportion of directors sitting on the boards of other companies have positive association with firm performance and financial management decisions.…”
Section: Board Expertise and Firm Performancementioning
confidence: 99%